Exploration the Ethnoscience of Gasing Game from Malay Riau Culture and its Potential for Physics Learning - Elviana, T.; Liliawati, W.; Sriyati, S. (Universitas Negeri Yogyakarta, 2024)
Gasing is a traditional game played by the Malay people of Riau, crafted from wood shaped like an inflated fruit, with a rope made from bark. This game is played by the Malay community in Riau to spend time with friends and to celebrate special occasions in the province. The research explored the methods of making and playing gasing by the Malay people of Riau and analyzed the physics concepts involved in the game. This qualitative study employed a literature review, observation, and interviews. The literature review examines Malay culture and gasing games. Observations were conducted in Siak Regency to directly observe the gasing games, including the tools and materials used, the game rules, and player interactions. Interviews with cultural experts provided insights into the cultural significance and traditional knowledge of the Malay community about the game. The findings reveal that gasing is made using merbau wood (Intsia bijuga) and bebaru bark (Thespesia populnea). In play gasing, the rope is wound around the body of the gasing, and the player takes a stance holding the gasing. The Gasing is then thrown to the ground with a sharp jerk of the rope, causing it to spin rapidly and for a long duration. Observations identified several physics concepts in the game, including balance, mass distribution, friction force, moment of inertia, rotational motion, angular momentum, kinetic energy, and surface area. The application of physics concepts in gasing highlights its potential as a valuable resource for ethnoscience-based physics learning.